Formation of cluster structures on thermoexfoliated graphite by electrochemical method - Sidorenko, I. G.; Ogenko, V. M.; Zagorovsky, G. M.; Prikhod'ko, G. P. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2002)
Nickel-plating thermoexfoliated graphite particles were prepared by cathodic polarization of three-dimensional electrodes in diluted nickel sulphate aqueous solutions. X‑ray photoelectron spectroscopy and X-ray diffraction techniques were employed for analysis of the particles surface. It has been found that oxidation process of the electrodeposited nickel clusters occurs due to their high reactivity. The presence of essential amounts of bound oxygen on surface of thermoexfoliated graphite particles was demonstrated by cyclic voltammetry and X-ray photoelectron spectroscopy methods. The role of oxygen‑containing groups on the surface of thermoexfoliated graphite in the processes of adsorption and subsequent reduction of nickel ions at cathodic polarization as well as the behaviour in neutral aqueous solutions of natural graphite electrodes, intercalated with sulfuric acid and thermoexfoliated, are discussed.